Analisis Karakter Organisasi Tenaga Kependidikan UNIKA De La Salle Manado menggunakan Macroergonomic Organizational Questionaire Survey - Tryadi; Ronald Albert Rachmadi (Universitas Katolik Musi Charitas, 2020)
Organizational culture is a system of disseminating trust and values that develops in an organization and directs the behavior of its members. De La Salle Catholic University of Manado is one of the educational institutions that has the motto